2022
DOI: 10.1038/s41385-021-00446-y
|View full text |Cite
|
Sign up to set email alerts
|

The scaffold-dependent function of RIPK1 in dendritic cells promotes injury-induced colitis

Abstract: Receptor interacting protein kinase 1 (RIPK1) is a cytosolic multidomain protein that controls cell life and death. While RIPK1 promotes cell death through its kinase activity, it also functions as a scaffold protein to promote cell survival by inhibiting FADD-caspase 8-dependent apoptosis and RIPK3-MLKL-dependent necroptosis. This pro-survival function is highlighted by excess cell death and perinatal lethality in Ripk1−/− mice. Recently, loss of function mutation of RIPK1 was found in patients with immunodef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…RIPK1 E-KO mice (with the epidermis-specific RIPK1-knockout) suffer from skin inflammation because of ZBP1-dependent keratinocyte necroptosis [ 149 , 152 ]. The dendritic cell (DC)-specific RIPK1 −/− mice with loss of RIPK1 kinase activity in other cells, exhibit spontaneous colonic inflammation relied on ZBP1-RIPK3 necrosome [ 153 ]. Advanced research indicated that the Zα2 and RHIM1 of ZBP1 are vital for this RIPK1 −/− caused spontaneous necroptosis, and endogenous retroviruses (ERV)-derived complementary reads were detected in epidermal RNA [ 15 , 58 , 154 ] ( Figure 4 ).…”
Section: Zbp1 Signaling In Auto-inflammatory Diseasesmentioning
confidence: 99%
“…RIPK1 E-KO mice (with the epidermis-specific RIPK1-knockout) suffer from skin inflammation because of ZBP1-dependent keratinocyte necroptosis [ 149 , 152 ]. The dendritic cell (DC)-specific RIPK1 −/− mice with loss of RIPK1 kinase activity in other cells, exhibit spontaneous colonic inflammation relied on ZBP1-RIPK3 necrosome [ 153 ]. Advanced research indicated that the Zα2 and RHIM1 of ZBP1 are vital for this RIPK1 −/− caused spontaneous necroptosis, and endogenous retroviruses (ERV)-derived complementary reads were detected in epidermal RNA [ 15 , 58 , 154 ] ( Figure 4 ).…”
Section: Zbp1 Signaling In Auto-inflammatory Diseasesmentioning
confidence: 99%
“…Our study showed no alteration in disease presentation in MLDSTZ- Ripk1 S25D/S25D compared to MLDSTZ- Ripk1 +/+ and RIPK1 enzymatic activation was not detected in islets of hyperglycemic mice subjected to MLDSTZ, demonstrating that RIPK1 kinase had no relevance in the dynamics of immune-mediated diabetes development. This lack of phenotype may reflect other studies which showed that dysfunctional immune responses were related to aberrant RIPK1 (prosurvival) scaffold function, independent of kinase activity [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 93%
“…Complex II activates caspase-8 activation and promotes apoptosis 36 . RIPK1 acts as a scaffolding www.nature.com/scientificreports/ protein that inhibits apoptosis in FADD-caspase8-dependent cells and RIPK3-MLKL-dependent cells and promotes cell survival 46 .…”
Section: Discussionmentioning
confidence: 99%